Why Cooperate? Public Goods, Economic Power, and the Montreal Protocol - Beron, Kurt J.; Murdoch, James C.; Vijverberg, Wim P. M. (The Review of Economics and Statistics, 2003)
This paper develops a correlated probit model to describe dichotomous choices that may contain a public-goods component or some other forms of interdependency. The key contribution of the paper is to formulate tests for interdependent behavior among agents. In particular, we examine the decisions by nations whether or not to ratify the Montreal Protocol on Substances that Deplete the Ozone Layer. Specifically, we reject free riding as a motive for not ratifying the Protocol, and we find little evidence that individual nations were influenced by the behavior of their largest trading partners. Hence, the data suggest that, with respect to the Montreal Protocol, most nations acted without regard for the actions of other nations.